2007
DOI: 10.1177/1534735406298258
|View full text |Cite
|
Sign up to set email alerts
|

Surviving Against All Odds: Analysis of 6 Case Studies of Patients With Cancer Who Followed the Gerson Therapy

Abstract: A considerable number of patients with cancer have used or are using the Gerson therapy, an alleged anticancer metabolic diet. However, there is almost no scientific support for this regimen. Hence, the present case review study of 6 patients with metastatic cancer who used the Gerson therapy aims at critically evaluating each case to derive some valid interpretations of its potential effect. All 6 cases had a cancer diagnosis with poor prognosis. Despite the presence of some confounding variables, it seems th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…In her qualitative interview study on exceptional cancer survivorship, Young defined cancer survival as "having survived beyond a medical prognosis of less than 20 percent chance of being cancer symptom free at the time of the interview." 22(p5) In addition, regardless of the specific research design, CAM use is rarely systematically monitored in studies on exceptional recoveries (with some notable exceptions 23,24 ). This is noteworthy because several studies have found that patients with reported exceptional recoveries have used CAM.…”
Section: Introductionmentioning
confidence: 99%
“…In her qualitative interview study on exceptional cancer survivorship, Young defined cancer survival as "having survived beyond a medical prognosis of less than 20 percent chance of being cancer symptom free at the time of the interview." 22(p5) In addition, regardless of the specific research design, CAM use is rarely systematically monitored in studies on exceptional recoveries (with some notable exceptions 23,24 ). This is noteworthy because several studies have found that patients with reported exceptional recoveries have used CAM.…”
Section: Introductionmentioning
confidence: 99%
“…However, no randomized clinical trial have con fi rmed these fi ndings. Molassiotis et al reported a case review of six patients with advanced cancer (Molassiotis and Peat 2007 ) . The authors reported prolonged survival; however, confounding variables preclude the study from supporting further research.…”
Section: Gerson Dietmentioning
confidence: 98%
“…Befragungen an Krebskranken haben gezeigt, dass diese v. a. in den ersten Monaten nach der Diagnose hoch motiviert sind, ihren Lebensstil und ihre Ernährungsweise zu ändern. Dieses Potenzial sollte genutzt werden, d. h. es sollten im Interesse von Krebskranken Studien zur therapeutischen Wirksamkeit bestimmter Krebsdiäten und v. a. der Gerson-Therapie durchgeführt werden [8].…”
Section: Ernährung Beeinflusst Verlauf Einer Krebserkrankungunclassified